2021
DOI: 10.1002/acn3.51371
|View full text |Cite
|
Sign up to set email alerts
|

GGC repeat expansions in NOTCH2NLC causing a phenotype of distal motor neuropathy and myopathy

Abstract: Background: The expansion of GGC repeat in the 5' untranslated region of the NOTCH2NLC has been associated with various neurogenerative disorders of the central nervous system and, more recently, oculopharyngodistal myopathy. This study aimed to report patients with distal weakness with both neuropathic and myopathic features on electrophysiology and pathology who present GGC repeat expansions in the NOTCH2NLC. Methods: Whole-exome sequencing (WES) and long-read sequencing were implemented to identify the cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
(109 reference statements)
0
19
0
Order By: Relevance
“…In this study, we screened the STR variants in dHMN patients, and identified GGC expansion in NOTCH2NLC in two autosomal dominant families and CAG expansion in ATNX2 in a patient with dHMN‐plus cerebellar ataxia. As we discussed in a previous study, 11 the GGC repeat expansion in the NOTCH2NLC has been associated with a new type of hereditary distal neuromyopathy based on a common pathological basis of widespread eosinophilic intranuclear inclusions in both nerves and muscles. Herein, we found that the GGC expansion in NOTCH2NLC can be responsible to a part of patients with dHMN with minor subclinical sensory abnormalities, of which the electrophysiological changes indicated both axonal and demyelinating involvements, and the clinical features showed some extra‐motor neuropathy symptoms such as tremor, dry cough, urinary incontinence, or headache.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In this study, we screened the STR variants in dHMN patients, and identified GGC expansion in NOTCH2NLC in two autosomal dominant families and CAG expansion in ATNX2 in a patient with dHMN‐plus cerebellar ataxia. As we discussed in a previous study, 11 the GGC repeat expansion in the NOTCH2NLC has been associated with a new type of hereditary distal neuromyopathy based on a common pathological basis of widespread eosinophilic intranuclear inclusions in both nerves and muscles. Herein, we found that the GGC expansion in NOTCH2NLC can be responsible to a part of patients with dHMN with minor subclinical sensory abnormalities, of which the electrophysiological changes indicated both axonal and demyelinating involvements, and the clinical features showed some extra‐motor neuropathy symptoms such as tremor, dry cough, urinary incontinence, or headache.…”
Section: Discussionmentioning
confidence: 69%
“…Nevertheless, it still remains difficult and elusive to genetic diagnosis of dHMN, because the causative variants have been identified in only 20.0–47.8% of affected index patients with different ethnic origins 6–10 . Recently, GGC repeat expansion in the 5′ untranslated region (5’UTR) of the NOTCH2NLC gene has been associated with distal motor neuropathy and rimmed vacuolar myopathy 11 . Additionally, some patients with CAG repeat expansion in the Ataxin‐2 (ATXN2) gene also can affect motor neuropathy independently 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Another Chinese study reported 3 unrelated patients with NOTCH2NLC GGC repeat expansions manifesting with distal motor neuropathy and rimmed vacuolar myopathy. 16 All patients presented with progressive weakness affecting predominantly distal lower limb muscles. In the present study, the 7 patients with NOTCH2NLC GGC repeat expansions had very mild or absent motor symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The GGC repeat expansion in the 59 untranslated region of NOTCH2NLC was recently identified as the cause of neuronal intranuclear inclusion disease (NIID), [5][6][7] a sporadic or autosomal-dominantly inherited neurodegenerative disease characterized by the eosinophilic, ubiquitin-and p62-positive intranuclear inclusions in cells of the CNS, peripheral nervous system, skin, and visceral organs. 8 There is a broad spectrum of clinical manifestations of NIID, including a diverse combination of cognitive impairment, 7,8 parkinsonism, 7,9 cerebellar ataxia, 10,11 encephalitis-like episodes, 8,12 tremor, 13,14 myopathy, 15,16 and peripheral neuropathy. 16,17 However, peripheral neuropathy was rarely reported as the main presentation of NIID.…”
mentioning
confidence: 99%